Hubungan Jenis Kelamin dengan Kejadian Dislipidemia pada Rumah Sakit Umum Daerah Cibabat Kota Cimahi - Nysa Ro Aina Zulfa; Dony Septriana Rosady (Yayasan Literasi Sains Indonesia, 2025)
Dyslipidemia is one of the main risk factors for cardiovascular disease, which causes more than 17 million deaths globally each year. In Indonesia, the prevalence of dyslipidemia has shown a significant increase, particularly among the productive age population. Although there are indications of differences in prevalence based on gender, scientific evidence remains inconsistent. Therefore, this study aims to analyze the relationship between gender and the occurrence of dyslipidemia in the adult population. This research employed a cross-sectional study design with a quantitative approach, using secondary data from the medical records of adult patients at the Outpatient Department of RSUD Cibabat, Cimahi City, in 2022. A total of 151 subjects were selected based on predefined inclusion and exclusion criteria. Data analysis was performed using the chi-square test and prevalence ratio (PR) calculation, with the assistance of SPSS version 30. Out of the 151 respondents, 76 individuals (50.3%) were identified as having dyslipidemia. The analysis revealed a significant association between gender and the incidence of dyslipidemia (p = 0.00), with males having a 2.23 times higher risk (PR = 2.23; 95% CI: 1.54–3.24) compared to females. There is a statistically significant relationship between gender and the occurrence of dyslipidemia, with a higher prevalence observed in males. This disparity may be influenced by biological, hormonal, and lifestyle factors. These findings support the need for promotive and preventive strategies that take gender aspects into account, including nutritional education, behavior modification, and early screening to reduce the risk of cardiovascular diseases associated with dyslipidemia.